Nickel and Zinc sulfide nanoparticles and thin films prepared from substituted Thiourea based complexes - Jawore, Abera (Vaal University of Technology, 2022)
Nanomaterials have attracted a great attention in this generation. Nanotechnology is currently one of the most advancing technologies utilized in many fields such as in semiconductors, solar cells medicine, agriculture, photovoltaic cell, sensors, and electroluminescent. Various methods have been employed to synthesize metal sulfide nanomaterials, however, many of the present methods use toxic and expensive starting materials which bring the problems into the society. The advancement of nanotechnology makes life better and brings about new inventions that can solve many problems in our daily lives. Thin films also have many benefits in our days, such as solar cell semiconductors, minimizing environmental pollution by replacing fuel gas. The combination of nanomaterials and thin films are core of civilization, green chemistry, and energy source. This study aimed to investigate the effect of different parameters such as reaction temperature, concentration of precursor, and reaction time on the physical properties of zinc sulfide (ZnS) and nickel sulfide (NiS) nanoparticles. The nanoparticles were synthesized from (Z)-2-(pyrrolidin-2- ylidene) thiourea zinc (II) complex and (Z)-2-(pyrrolidin-2-ylidene) thiourea nickel(II) complex using the hydrothermal method. The synthesized nanoparticles were capped using hexadecylamine (HDA) and trioctylphosphine oxide (TOPO). The synthesized nanoparticles were characterized using various techniques such as transmission electron microscopy (TEM), X-ray diffraction (XRD), UV-Vis absorption spectroscopy, and photoluminescence spectroscopy. The TEM images of the HDA capped zinc sulfide nanoparticles synthesized from 0.5 mg of the precursor showed quite agglomerated, rod-like structures, small and size particles with an average particle size of 4.46 nm. The HDA capped zinc sulfide nanoparticles synthesized from 1 mg of precursors showed polydispersity small spherical and agglomerated particles. The TEM images of TOPO capped zinc sulfide nanoparticles synthesized from 0.5 mg of the precursor showed small spherical sized particles with an average particle size of 2.16 nm and 2.86 nm. It was noted that the size of the particles increases when the concentration of the increases. The UV-Vis spectra of the HDA capped ZnS nanoparticles revealed two narrow absorption peaks at 304 nm and 307 nm, while the TOPO capped ZnS nanoparticles had an absorption peak of 301 nm. The photoluminescence spectra of both capped ZnS nanoparticles revealed two narrow emission peaks at 405 nm and 445 nm, and 409 nm and 433 nm respectively. The XRD patterns of both capped ZnS nanoparticles revealed mainly peaks at 21.2º, 23.3º, 25.4º, 27.1º, and 29.7º corresponding to the (300), (400), (401), (402) and (403) planes of the hexagonal phase. The TEM images of the HDA capped NiS nanoparticles revealed irregular, agglomerated particles in the size range of 6.31 nm to 7.46 nm, while the TOPO capped NiS nanoparticles showed an average particle size of 6.31 nm. The XRD patterns of the HDA capped NiS nanoparticles exhibited a hexagonal phase, as evidenced by the peaks at 20 º (100), 26.4º (101), 32.6º (102) and 49.2º (104). The TOPO capped NiS nanoparticles showed peaks at 30.22º (111), 32.35º (200), 34.19º (210), 38.96º (211), 44.77º (220), 50.94º (311), and 59.58º (023), which correspond to the nickel sulfide cubic phase. This study provides a better understanding of the synthesis, characterization and properties of ZnS and NiS nanoparticles and thin films.
M. Tech. (Department of Chemistry, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Nanomaterials; Nanotechnology; Nickel and Zinc Sulfide Nanoparticles; Thiourea based complexes; Semiconductor; Catalytic activity; Solar cells; Metal sulfide nanoparticles; Synthesis of metal sulfide nanoparticles; Zinc sulfide and nickel sulfide thin films; Adsorption; Dissertations, Academic -- South Africa.; Nanoparticles.; Nanotechnology.; Nanostructured materials.